2006
DOI: 10.1086/507271
|View full text |Cite
|
Sign up to set email alerts
|

Cosmological Evolution of the Duty Cycle of Quasars

Abstract: Quasars are powered by accretion onto supermassive black holes, but the problem of the duty cycle related to the episodic activity of the black holes remains open as one of the major questions of cosmological evolution of quasars. In this Letter, we obtain quasar duty cycles based on analyses of a large sample composed of 10,979 quasars with redshifts $z\le2.1$ from the Sloan Digital Sky Survey (SDSS) Data Release Three. We estimate masses of quasar black holes and obtain their mass function (MF) of the presen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 27 publications
5
68
0
Order By: Relevance
“…It has been found that black hole duty cycles follow the history of the star formation rate density (Wang et al 2006). The above scenario then implies that both the black hole activities and the starbursts are episodic (Davies et al 2006).…”
Section: No 2 2007 Suppressed Star Formation L145mentioning
confidence: 85%
“…It has been found that black hole duty cycles follow the history of the star formation rate density (Wang et al 2006). The above scenario then implies that both the black hole activities and the starbursts are episodic (Davies et al 2006).…”
Section: No 2 2007 Suppressed Star Formation L145mentioning
confidence: 85%
“…Supernova explosions observed today are related to their past star formation history, in that a progenitor with mass M * will explode t(M * ) years later after its formation, with t(M * ) = 13(M * /M ) −2.5 . If a constant star formation rate of 10 M yr −1 such as in SDSS J0802+5513 holds for the past 100 Myr, i.e., the typical AGN life cycle (Wang et al 2006), all star with mass larger than 7 M will explode today. Assuming a Salpeter initial mass function, a large fraction f c = 0.38 of star formation mass will be recycled into the ISM ).…”
Section: Origin Of the Absorption Gasmentioning
confidence: 99%
“…Galaxies with AGNs that outshine their host galaxies ("quasars") are ubiquitous at  z 1 (e.g., Pâris et al 2017), i.e., during the epoch in which the universe formed most of its stars (Madau & Dickinson 2014). However, quasars are transient phenomena with duty cycles that are difficult to measure (Martini & Schneider 2003;Wang et al 2006;Shen et al 2007;Shankar et al 2010;Schmidt et al 2017). AGNs also acts as a source of feedback, injecting energy both radiatively and mechanically back into their immediate environments.…”
Section: Introductionmentioning
confidence: 99%